Clinical value of serum osteocalcin (BGP),bone alkaline phosphatase (BALP), N-terminal propeptide of type 1 procollagen (P1NP)in the CREFG were visibly increased, while type I collagen carboxy terminal peptide β special sequence (β-CTX)was visibly decreas: serum BGP, BALP, P1NP, β-CTX, CRP; B: IL-6; C: IL-1β; D: TNF-α - Li, Lingfeng (Journal of Medical Biochemistry, 2025)
Introduction: It aimed to explore the effectiveness and safety of closed reduction and internal fixation (CRIF) and closed reduction and external fixation (CREF) in treating tibiofibular fracture, as well as their impact on patients’ bone metabolism and inflammatory responses.Material and Method: A retrospective collection of 95 cases of tibiofibular fracture patients’ clinical data was conducted and the subjects were grouped: CRIF group (CRIFG) and CREF group (CREFG). Distinctions in clinical efficacy, visual analogue scale (VAS) scores, serum bone metabolism indicators, serum inflammatory cytokines, generic quality of life inventory-74 (GQOLI-74) scores, and adverse reactions (AR) were compared.Result: The total clinical efficacy rates of the CRIFG and CREFG were 80.49% (33/41) and 85.19% (46/54), respectively(P >0.05). However, compared with the CRIFG, in the CREFG, the VAS scores were visibly reduced, and the GQOLI-74 scores in each dimension were visibly increased; serum osteocalcin (BGP),bone alkaline phosphatase (BALP), N-terminal propeptide of type 1 procollagen (P1NP)in the CREFG were visibly increased, while type I collagen carboxy terminal peptide β special sequence (β-CTX)was visibly decreased; C-reactive protein (CRP), interleukin-6 (IL-6), IL-1β, tumor necrosis factor-α (TNF-α)in the CREFG were visibly reduced; The total AR rates in the CRIFG and CREFG were 31.71% (13/41) and 18.52% (10/54), respectively(P
Keywords: serum BGP, BALP, P1NP, β-CTX, CRP; B: IL-6; C: IL-1β; D: TNF-α, tibiofibular fracture; closed reduction; internal fixation; external fixation; bone metabolism; inflammation